2014
DOI: 10.1037/a0036979
|View full text |Cite
|
Sign up to set email alerts
|

The role of age and motivation for the experience of social acceptance and rejection.

Abstract: A study with n = 55 younger (18-33 years, M = 23.67) and n = 58 older (61-85 years, M = 71.44) adults investigated age-related differences in social approach and avoidance motivation and their consequences for the experience of social interactions. Results confirmed the hypothesis that a predominant habitual approach motivation in younger adults shifts toward a stronger avoidance motivation in older adults. Moreover, age and momentary motivation predicted the experience of an actual social interaction. Younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…This negative effect of social identity threat on social approach motivation is important, as social approach motivation is crucial for establishing and maintaining positive social relationships (Gable, 2006), which, in turn, is essential for psychological and physical health (Umberson et al, 2010). This is particularly true in young adulthood because establishing a personal and professional social network is an important developmental task in this age group (Nikitin, Schoch, & Freund, 2014). As earlier research has shown that social networks are related to individual and group performance (e.g., Sparrowe, Liden, Wayne, & Kraimer, 2001), impoverished social networks in academic or occupational circles might lead to a downward spiral, hampering stereotyped individuals' performance and work-related success.…”
Section: Discussionmentioning
confidence: 99%
“…This negative effect of social identity threat on social approach motivation is important, as social approach motivation is crucial for establishing and maintaining positive social relationships (Gable, 2006), which, in turn, is essential for psychological and physical health (Umberson et al, 2010). This is particularly true in young adulthood because establishing a personal and professional social network is an important developmental task in this age group (Nikitin, Schoch, & Freund, 2014). As earlier research has shown that social networks are related to individual and group performance (e.g., Sparrowe, Liden, Wayne, & Kraimer, 2001), impoverished social networks in academic or occupational circles might lead to a downward spiral, hampering stereotyped individuals' performance and work-related success.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large study found that although negative social interactions decrease with age, the association between negative social interactions and physical health increases across adulthood (Hakulinen et al, ). Accordingly, older adults are more motivated to maintain social harmony and to avoid or reduce negative social encounters than younger adults (Birditt et al, ), report higher levels of well‐being when they successfully avoided negative social encounters (Charles, Piazza, Luong, & Almeida, ), and report lower levels of well‐being when they were not able to avoid a negative social encounter (Nikitin, Schoch, & Freund, ). Do these developmental changes affect peoples' social approach and avoidance goals?…”
Section: Social Development Across Adulthoodmentioning
confidence: 99%
“…Despite its positive association with responsiveness, self-reported social avoidance motivation was negatively associated with subjective well-being. One possible explanation for this counterintuitive finding is that avoidance motivation is associated with focus on the negative aspects of the situation (e.g., Nikitin & Freund, 2014) and, thereby, leads to a negative experience of a given situation, irrespective of the level of responsiveness.…”
Section: Social Motivation and Subjective Well-beingmentioning
confidence: 99%